Preparation, Identification, and Enzyme Inhibition Kinetic Analysis of Phosvitin α-Amylase Inhibitory Peptides - Tianrui XUE; Binfei LÜ; Mingran ZHANG; Can LI; Xiaowei ZHANG (Shipin gongye ke-ji)
To explore the inhibiting effect of phosvitin phosphopeptide (PPP) on α-amylase, enabling it to regulate blood glucose levels and alleviate type Ⅱ diabetes mellitus. This study employed enzymatic hydrolysis of phosvitin with the inhibition rate of α-amylase as an index, followed by enzyme inhibition kinetics experiments to analyze the inhibitory type of PPP on α-amylase. LC-MS identification was conducted, and molecular docking was performed to screen for highly active α-amylase inhibitory peptides, which were subsequently validated. The results showed that optimal enzymatic hydrolysis conditions involved initial hydrolysis with trypsin (7000 U/g), followed by pepsin (60000 U/g) for 6 h each. The prepared PPP exhibited the highest α-amylase inhibition rate 70.69%±1.71% at a concentration of 7.81×10−3 mg/mL. PPP acted as a mixed-type inhibitor. Two novel highly active α-amylase inhibitory peptides FGTEPDAK and IWGR were identified and screened, exhibiting IC50 values of (0.80±0.14)×10−3 mg/mL and (1.80±0.31)×10−3 mg/mL, respectively. Both extremely significantly lower than the positive control acarbose's IC50 value (3.17±0.47)×10−3 mg/mL (P<0.01). This study highlights the potential use of PPP as a new hypoglycemic substance in developing functional foods for alleviating type Ⅱ diabetes mellitus.